A case report of lumbar hernia - Sachar, Rupali Kaur; Rao, Hemshankar; Yadav, Sunita; D., Apurva (International Surgery Journal, 2022)
Lumbar hernia is one of the rare cases that most surgeons are not exposed to. Hence the diagnosis can be easily missed. This leads to delay in the treatment causing increased morbidity. We report a case of lumbar hernia in a middle-aged man. Clinical and MRI findings were correlated to reach the diagnosis. We also highlighted the types, the process of diagnosis and the surgical repair of lumbar hernias.